1998
DOI: 10.1111/j.1525-1470.1998.tb01357.x
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL OUTCOME AND COST ANALYSIS OF ISOTRETINOIN VERSUS CONVENTIONAL REGIMENS IN THE TREATMENT OF MODERATE ACNE VULGARIS IN MALE PATIENTS

Abstract: Correspondence 329(3), we still think that our case is compatible with clear cell papulosis.The main difference between our case and the previous cases is the location of the lesions, as we have already described in our article (3). The previous cases of clear cell papulosis occurred most commonly on the lower abdomen and usually along the milk line (1,2), but our case occurred on the lumbar area and buttocks (3). However, not all of the previously described lesions occurred exactly along the milk line, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Some of these studies cited that early use of oral isotretinoin versus other treatment regimens had a higher cost in the short term but had lower longterm costs, a shorter time to the goal of treatment, more effectiveness by clinical measures, decreased rates of relapse and scarring, and benefits for earlier use and use in mild to moderate acne (18)(19)(20)(21). This is in contrast to a managed care study from the United States which showed a 35% reduction in per member per month cost after restricting oral isotretinoin to patients until they were determined to be unresponsive to topical retinoids, at least two other topical medications, and two oral antibiotics (27).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Some of these studies cited that early use of oral isotretinoin versus other treatment regimens had a higher cost in the short term but had lower longterm costs, a shorter time to the goal of treatment, more effectiveness by clinical measures, decreased rates of relapse and scarring, and benefits for earlier use and use in mild to moderate acne (18)(19)(20)(21). This is in contrast to a managed care study from the United States which showed a 35% reduction in per member per month cost after restricting oral isotretinoin to patients until they were determined to be unresponsive to topical retinoids, at least two other topical medications, and two oral antibiotics (27).…”
Section: Discussionmentioning
confidence: 98%
“…However, other studies in the literature have taken a stricter dollar-cost per effect approach in attempting to evaluate cost-effectiveness. A good example of this is the US study from 1998 which compared direct cost and clinical outcome (20). This study assessed the direct costs of oral isotretinoin treatment versus the direct costs of conventional therapy and compared them with an outcome measured by complete clearing of acne (Table VI).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations